2020
DOI: 10.3389/fphar.2020.594562
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetics and Model-Based Dosing Optimization of Teicoplanin in Pediatric Patients

Abstract: Objectives: The pharmacokinetics (PK) of teicoplanin differs in children compared with adults. Our aim was to determine the PK of teicoplanin in an Asian pediatric population and to optimize dosage regimens.Methods: This was a retrospective PK study and all the data were collected from hospitalized children. We developed a population PK model using sparse data, and Monte Carlo simulation was used to assess the ability of standard teicoplanin regimen and other different dosage regimens. The optimal dosing regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 47 publications
1
17
0
Order By: Relevance
“…In healthy adults, the theoretical CL R of teicoplanin by filtration was 1.01 L/h, which was close to the 0.98 L/h value reported in the literature 31 . The mean CL R (0.701 L/h) in children with normal renal function was similar to that of Chinese children (0.694 L/h), 10 but higher than that of French children with malignant hematological disease (0.485/h) 7 . Specifically, the predicted data were reasonably consistent with the observed data, and the predictions of PK values (AUC, C max ) were within 1.36‐fold error.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In healthy adults, the theoretical CL R of teicoplanin by filtration was 1.01 L/h, which was close to the 0.98 L/h value reported in the literature 31 . The mean CL R (0.701 L/h) in children with normal renal function was similar to that of Chinese children (0.694 L/h), 10 but higher than that of French children with malignant hematological disease (0.485/h) 7 . Specifically, the predicted data were reasonably consistent with the observed data, and the predictions of PK values (AUC, C max ) were within 1.36‐fold error.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, our analysis showed that the standard dosing regimen results in underdosing based on the PK/PD index used for infections in the upper MIC range, and a previously empirical study of Asian pediatric patients confirms this viewpoint. 7,10 The developed teicoplanin PBPK model may offer significant implications for promoting reasonable medication and guaranteeing therapeutic effectiveness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, our results indicated that the teicoplanin trough concentrations of patients with ECMO and CRRT therapy showed a downward trend. In our study, pediatric patients (aged <14 years) were excluded because of their diverse pharmacokinetics ( 36 ). According to the medication instruction, no dose adjustment is required for the elderly patients.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al reported population pharmacokinetics and initial dose optimization of sirolimus improving drug blood level for seizure control in pediatric patients with tuberous sclerosis complex (Xiao Chen et al, 2021). Zhang et al (2020) reported population pharmacokinetics and model-based dosing optimization of teicoplanin in pediatric patients. Based on these precedents, population pharmacokinetics and Monte Carlo simulations were used to recommend optimal initial dosing of tacrolimus in children with SCID undergoing HSCT in our study.…”
Section: Discussionmentioning
confidence: 99%